2016
DOI: 10.1038/srep24931
|View full text |Cite
|
Sign up to set email alerts
|

Glycoengineered Outer Membrane Vesicles: A Novel Platform for Bacterial Vaccines

Abstract: The World Health Organization has indicated that we are entering into a post-antibiotic era in which infections that were routinely and successfully treated with antibiotics can now be lethal due to the global dissemination of multidrug resistant strains. Conjugate vaccines are an effective way to create a long-lasting immune response against bacteria. However, these vaccines present many drawbacks such as slow development, high price, and batch-to-batch inconsistencies. Alternate approaches for vaccine develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
93
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(95 citation statements)
references
References 48 publications
1
93
0
1
Order By: Relevance
“…We previously demonstrated that the C. jejuni N-glycan is an effective antigen in various vaccine formulations, including glycoprotein conjugates, E. coli surface expression carriers, and outer membrane vesicles (36,42). To date, the live E. coli vaccine comprised of the N-glycan attached to the LOS core demonstrated the greatest success in significantly reducing C. jejuni colonization in leghorn chicken challenge studies (36).…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that the C. jejuni N-glycan is an effective antigen in various vaccine formulations, including glycoprotein conjugates, E. coli surface expression carriers, and outer membrane vesicles (36,42). To date, the live E. coli vaccine comprised of the N-glycan attached to the LOS core demonstrated the greatest success in significantly reducing C. jejuni colonization in leghorn chicken challenge studies (36).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, rigorous evaluation of prebiotic and probiotic outcomes (149) and establishment of realistic production benchmarks are mandatory before there will be further adoption by industry. Alternatively, the engineering of intestinal microorganisms, such as chimeric live vaccines (150,151), CRISPR-based genome editing (152), and synthetic biology of secondary metabolism (153), holds vast potential and may ultimately transform how food is produced in the future.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Outer membrane vesicles (OMVs) are protrusions of the outer membrane of gram‐negative bacteria, which have become popular as a vaccine delivery platform over the past few years. In their recent work, Price et al . described non‐pathogenic E. coli strains engineered to express surface glycans from other bacterial pathogens on their membranes.…”
Section: Multivalency In Immune Cell Modulationmentioning
confidence: 99%